2020
DOI: 10.1021/acsami.9b20831
|View full text |Cite
|
Sign up to set email alerts
|

Interface Engineering of Imidazolium Ionic Liquids toward Efficient and Stable CsPbBr3 Perovskite Solar Cells

Abstract: The defect passivation of perovskite films is an efficacious way to further boost the power conversion efficiency (PCE) and long-term stability of perovskite solar cells (PSCs). In this work, ionic liquids (ILs) of 1-butyl-2,3-dimethylimidazolium chloride ([BMMIm]Cl) are used as a modification layer in perovskite films in carbon-based CsPbBr 3 PSCs without a hole-transporting material (HTM) for passivating the surface defects. The preliminary results demonstrate that the [BMMIm]Cl modifier passivates the surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
120
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(127 citation statements)
references
References 52 publications
(65 reference statements)
7
120
0
Order By: Relevance
“…[25] Generally, the growth of crystal grains perpendicular to the direction of the indium tin oxide (ITO)/TiO 2 substrate is more conducive to charge transfer. [26] This is also consistent with the vertical growth crystal grain morphology observed in the cross-sectional SEM image of CsPbIBr 2 in Figure 1c.…”
Section: Resultssupporting
confidence: 88%
“…[25] Generally, the growth of crystal grains perpendicular to the direction of the indium tin oxide (ITO)/TiO 2 substrate is more conducive to charge transfer. [26] This is also consistent with the vertical growth crystal grain morphology observed in the cross-sectional SEM image of CsPbIBr 2 in Figure 1c.…”
Section: Resultssupporting
confidence: 88%
“…It is remarkably efficient in suppressing the series resistance and improving the charge carriers’ dynamics by close contact modification between interlayers. [ 20 ] Figure 3b represents the current density–voltage ( J – V ) characteristics of MAPbI 3 PSCs with and without [BZTAm]Cl treatment, measured under standard simulated illumination of AM 1.5G (1000 Wm 2 ) and the corresponding device parameters are tabulated in Table 1 . The control device without [BZTAm]Cl modification acquired an average device PCE of 16.87% ± 1% with an open‐circuit voltage ( V OC ) of 1.07 ± 0.01 V, a current density ( J SC ) of 21.12 ± 1.29 mA cm −2 , and fill factor (FF) of 74% ± 1%.…”
Section: Resultsmentioning
confidence: 99%
“…[ 17 ] Moreover, previously reported work indicated that trap states mainly located at the interfaces of multilayers of whole device (called interface defects) and at the perovskite surface (called surface defects), which are effectively related to the energy level matching, hysteresis, charge carriers dynamics, and the long‐term environmental and operational stability. [ 18–22 ] Therefore, it is indispensable to explore an impressive way to diminish the defects, particularly at the interfaces, for acquiring the high‐efficient and stable PSCs. Currently, there are lots of approaches to improve the performance and stability of PSCs, containing additive engineering, using additive into a perovskite absorber layer and interface engineering, modifying the hole transport layer (HTL)/perovskite or perovskite/electron transport layer (ETL) interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of ionic liquids such as methylammonium acetate [193] , 1-methyl-3imidazolium iodide [194] as 1-alkyl-4-amino-1,2,4-triazolium, [195],1-hexyl-3methylimidazolium chloride, [196] and 1-ethylpyridinium chloride [197], are incorporated in the perovskite solution which requires complex optimization processes as the blending system could undergo severe phase transition. The interface modification of CsPbBr 3 via incorporating Ionic liquid (IL) of 1-butyl-2,3-dimethylimidazolium chloride ([BMMIm]Cl) was studied by Zhang group [198]. In their study, they found out that the incorporation of ionic liquid modifier the surface defects of the films were passivated and the valence band of perovskite is shifted close to the work function of the carbon electrode, which substantially suppressed the radiative and improved energy-level matching, non-radiative charge recombination , and reduced energy loss.…”
Section: Ionic Liquids (Ils) Interface Engineeringmentioning
confidence: 99%